Bimbingan Kelompok dengan Teknik Problem Solving dalam Meningkatkan Penyesuain Diri di Lingkungan Baru - Asna; Najlatun Naqiyah; Endang Pudjiastuti Sartinah (Bidayatuna, 2022)
In addition to using policies from the government, there are also policies from the administrators of the pesantren, known as students who study in Islamic boarding schools. Many problems occur to students, especially new students who cannot adjust to their new environment. They will, have difficulties in social and learning. Group guidance services use problem-solving techniques expected to help students solve problems that occur, so that students are accustomed to solving their own problems. The author uses a pre-research method that collects various main informatprimaryabout hidden themes by using various sources. What needs to be observed is how the scheme works on the object, the environmental conditions, and also what problems are going on in the object; after the observation, the researcher interviewed the auto to know how the thing was. The aim was to find what obstapurposes and kinds of obstacles were, hota were who were threats involved,and how the concepts and methods were wanted t develop further.